Evaluación de las variables del desempeño cooperativo con enfoque en el buen vivir en la provincia de el Oro. - Guerrero Santana, Laura Mercedes (2017)
This research has as main objective the evaluation of the variables of the cooperative performance focus in the Good Living in the Cooperatives of Savings-Credit and Production in El Oro. Starting with the identification of the existing variables in the environment in order to structure an assessment tool suitable to its application to the managers, employees and business partners of these entities, to determine the behavior of these cooperatives against the Good Living of their associates. Applying this line of research, was essential the use of inductive, deductive, quantitative and qualitative methods among others, likewise, interview and survey techniques, and therefore the instruments that facilitated the collection of information from experts, as the use of coefficient of competences Kendall, Delphi and Togerson, tools, which contributed to a large extent to the achievement of results. In this sense, detected shortcomings that impeded the fulfilment of certain principles of Cooperativism, Popular and Solidarity Economy, Corporate Social Responsibility and Good Living through the Ishikawa diagram and QFD system, a plan of improvements to counteract the weaknesses found in the study of these cooperatives was developed, where it was demonstrated that in the field of Savings-Credit there were deficiencies in the commitment to the environment, as well as in the Production revealed shortcomings in the economic participation, solidarity and equitable distribution, autonomy and independence, in addition, in the education, training and information, therefore it is necessary to continue strengthening to these sectors focused in the Good Living.